2015
DOI: 10.1002/pro.2811
|View full text |Cite
|
Sign up to set email alerts
|

Structure of lpg0406, a carboxymuconolactone decarboxylase family protein possibly involved in antioxidative response from Legionella pneumophila

Abstract: Lpg0406, a hypothetical protein from Legionella pneumophila, belongs to carboxymuconolactone decarboxylase (CMD) family. We determined the crystal structure of lpg0406 both in its apo and reduced form. The structures reveal that lpg0406 forms a hexamer and have disulfide exchange properties. The protein has an all-helical fold with a conserved thioredoxin-like active site CXXC motif and a proton relay system similar to that of alkylhydroperoxidase from Mycobacterium tuberculosis (MtAhpD), suggesting that lpg04… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Gene Ontology (GO) predicted that TvCMD1 functions in electron transport, namely, it has peroxiredoxin activity [ 48 ]. Furthermore, non-canonical CMD has been demonstrated to have disulfide reductase or thioredoxin activities [ 31 , 32 ]. The putative cysteine residues were not found in the protein sequence, suggesting that neither electron transfer nor iron-sulfur cluster docking was employed by TvCMD1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene Ontology (GO) predicted that TvCMD1 functions in electron transport, namely, it has peroxiredoxin activity [ 48 ]. Furthermore, non-canonical CMD has been demonstrated to have disulfide reductase or thioredoxin activities [ 31 , 32 ]. The putative cysteine residues were not found in the protein sequence, suggesting that neither electron transfer nor iron-sulfur cluster docking was employed by TvCMD1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that non-canonical CMDs serve as disulfide reductase- and thioredoxin-like proteins [ 31 , 32 ]. To examine the probable function of TvCMD1, we divided the TvCMD1 sequence into two CMD signatures and aligned them with these CMDs.…”
Section: Sequence Analysis Of Tvcmd1mentioning
confidence: 99%
“…These are adhA, yraC , and yraA , which encode for an AdhC homolog, a γ-carboxymuconolactone decarboxylase, and a cysteine proteinase, respectively ( Huyen et al, 2009 ). YraC is proposed to be a component of protocateculate metabolism and a homolog of YraC from Legionella pneumophila has been shown to display peroxidase activity ( Huyen et al, 2009 ; Chen et al, 2015 ). How YraC contributes to the defense against formaldehyde toxicity remains to be defined.…”
Section: Genetic and Functional Basis For Formaldehyde Detoxificationmentioning
confidence: 99%
“…This subset of proteins included the protein with the highest abundance listed in lignin-amended conditions in both phases, which was annotated as a carboxymuconolactone decarboxylase (CMD) family protein (Pfam 02627). The CMD family of proteins is associated with aromatic degradation in aerobic bacteria, via the protocatechuate branch of the β-ketoadipate pathway, as well as antioxidant defense via peroxidase activity [42,43]. The CMD family protein identified in BRL6-1 contained an alkylhydroperoxidase (AhpD) domain and CXXC motif (log 2 fold-change of 8 and 7, respectively) (Fig 2A).…”
Section: Evidence Of Proton-relay System-related Enzyme For Lignin Dementioning
confidence: 99%
“…The CMD family protein identified in BRL6-1 contained an alkylhydroperoxidase (AhpD) domain and CXXC motif (log 2 fold-change of 8 and 7, respectively) (Fig 2A). Based on the CXXC motif, it is thought that the protein detected in BRL6-1 has AhpD-like activity [42]. AhpD is part of an antioxidant defense system that forms a complex with peroxiredoxin, AhpC.…”
Section: Evidence Of Proton-relay System-related Enzyme For Lignin Dementioning
confidence: 99%